Technical feasibility of genetically engineered cotton varieties expressing Cry proteins against Anthonomus grandis in the Sinú Valley, Colombia - Osorio-Almanza, Lorena; Burbano-Figueroa, Oscar; Martinez-Reina, Antonio (Universidad Pedagógica y Tecnológica de Colombia, 2018)
Anthonomus grandis and Spodoptera frugiperda are the main cotton pests in the Colombian Caribbean region, the main producer in the country. Controlling A. grandis accounts for 20% of the production costs. Cry proteins available nowadays in transgenic cotton cultivars are inefficient managing these pests; however, new Cry proteins have proven to have a toxic effect on A. grandis and S. frugiperda under in-vitro and in-planta conditions. Genes encoding these proteins can be inserted in cotton plants producing a new generation of transgenic plants highly useful in those regions severely affected by the boll weevil. The purpose of this study was to estimate the technical feasibility and challenges of developing new genetically engineered cotton varieties for controlling A. grandis and S. frugiperda. Four different technological scenarios for incorporating transgenic plants expressing Cry proteins with different pest control levels are proposed. These scenarios are based on published experimental evidence, and the potential effects on the cost structure of cotton production are estimated with the data gathered at a meeting with farmers. Development of transgenic cultivars expressing the Cry1Ia12 protein is the most cost-effective option. Considering the environmental conditions of the Sinu Valley, Cry1Ia12 insertion would reduce pest management costs in more than 40%.